You need to remember the definition of signum function such that:

`sgn x = {(-1, x<0), (0, x=0), (1, x>0):}`

You need to evaluate the integral `int_-1^2 sgn x dx` , hence, you need to split the integral in two integrals such that:

`int_-1^2 sgn x dx = int_-1^0 sgn...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to remember the definition of signum function such that:

`sgn x = {(-1, x<0), (0, x=0), (1, x>0):}`

You need to evaluate the integral `int_-1^2 sgn x dx` , hence, you need to split the integral in two integrals such that:

`int_-1^2 sgn x dx = int_-1^0 sgn x dx + int_0^2 sgn x dx `

`int_-1^2 sgn x dx = int_-1^0 -dx + int_0^2 dx`

Using the fundamental theorem of calculus yields:

`int_-1^2 sgn x dx = -x|_(-1)^0 + x|_0^2`

`int_-1^2 sgn x dx = (0 + (-1)) + 2 - 0`

`int_-1^2 sgn x dx = 2 - 1`

`int_-1^2 sgn x dx = 1`

**Hence, evaluating the definite integral of signum function yields `int_-1^2 sgn x dx = 1.` **